Strategi Pembelajaran Pendidikan Akhlak Di Kelas VIII Global SMP Muhammadiyah 7 Surakarta Tahun Pelajaran 2016-2017 - Dewi, Anggita Citra, Drs. Darojat Ariyanto, M.Ag (2017)
SMP Muhammadiyah 7 Surakarta is one of the first highschoolunder the auspices of the organization of Muhammadiyah. Differebt with the another educational institutions in general, SMP has one excellent class program that is a global classroom program. The purpose of this global class is to create a generation with global vision, but still have character and noble character and uphold the values of Islam. In order to achieve these goals, it requires PAI teachers who have some strategies in learning PAI especially morals. Therefore the authors want to do a research on the strategy of teachers PAI in moral learning in class VIII global SMP Muhammadiyah 7 Surakarta and want to know what are the factors supporting and inhibiting learning morals in class VIII global SMP Muhammadiyah 7 Surakarta. This type of research is field research (Field research) with qualitative research approach. The method used is the method of observation, interview and documentation. While the analysis that the researcher uses is descriptive analysis that is in the form of exposure of data in writing about the related data, both written and oral from the object of research that exist in lembagan. In this case the author describes thoroughly about the actual situation. The result of the research shows that the strategy done by PAI teacher in moral learning in class VIII global SMP Muhammadiyah 7 Surakarta is: a) to improve the quality of learning in the classroom. B) the procurement of the agenda book. C) exemplary and habituation done by teachers and schools. While the supporting factor in moral learning in class VIII global SMP Muhammadiyah 7 Surakarta is internal and external, and the factor of learning is not only morality factor found that is internal.